Affective Commitment to Organizations: A Comparison Study of Reverse Mentoring Versus Traditional Mentoring Among Millennials - Catrin Hechl (Bina Nusantara University, 2017)
A current topic of interest in management and organization research is the phenomenon of a generation shift in the workforce and how this shift will affect organizations in the near future. Millennials represent the largest generational cohort in the American workforce. Organizations find themselves challenged with retention efforts as Millennials tend to leave an organization after short tenures. The problem this study addressed is the high turnover rates among millennial employees. Specifically, it was unknown whether Millennials who received reverse mentoring evidenced greater affective commitment to the organization as compared to Millennials who received standard mentoring. The purpose of this study was to investigate the hypothesis that Millennials who received reverse mentoring evidenced greater affective commitment to the organization as compared to Millennials who received standard mentoring. A two group post-test only quasi-experimental design was conducted. A total of 90 participants (45 per group) completed the survey. The survey was conducted by Qualtrics, an online survey company. The sample population included male and female individuals, born between 1982 and 1998, employed by all types of organizations in the United States and participating in a mentoring program at the time the survey was taken. Affective commitment was greater in the reverse mentoring group (M = 36.683, SE = .959) compared to the traditional mentoring group (M = 34.984, SE = .959). However, after adjustment for quality of relationship (LMX) and length and frequency of mentoring (LFM) there was no statistically significant difference (p < .05) between traditional mentoring and reverse mentoring on affective commitment to the organization indicated by F(1,86) = 1.569, p = .214. Additional results of this study showed that two-thirds of the surveyed millennial employees had already exceeded the average length of employment of 12 to 18 months with the organization they were employed with at the time of the survey. This finding indicated the importance of investing in workplace relationships, such as mentoring, regardless of traditional or reverse.